DESIGN OF A GEOELECTRIC TOOL BASED ON PWM (PULSE-WIDTH MODULATION) - AKBAR (NIM: 90214022), MUHAMMAD
The need of geophysical survei equipment is very high, especially geoelectric tool. The high requirements of its equipment made geoelectric tool becomes very expensive. The way to overcome this problem is the idea to build own geoelectric tool. Geoelectric tool is a geophysics tool to determine electric current into the ground. Geoelectric tool injects a DC voltage of electric current, then the value of the potential difference in the ground will be known. The potential difference is measured using a voltmeter while DC voltage is measured using a power supply. Power supply used is based on PWM (pulse-Width Modulation) principle which can raise DC voltage by Modulation techniques. PWM is used as a booster amplifier because it provides a large enough DC voltage. Then, the function of the PWM is converted to power supply geoelectric because geoelectric tool requires a large DC voltage to inject currents on a long expanse. The advantages of geoelectric based PWM is more practical and cheaper than geoelectric based on trafo.